Training non-physicians to do endoscopy: Feasibility, effectiveness and cost-effectiveness. Issue 3 (June 2016) - Ruco, A.; Walsh, C.M.; Cooper, M.A.; Rabeneck, L.
Abstract: Colorectal cancer (CRC) is one of the most common cancers in women and men worldwide. Training non-physicians including nurses, nurse practitioners, and physician assistants to perform endoscopy can provide the opportunity to expand access to CRC screening as demand for endoscopic procedures continues to grow. A formal program, incorporating didactic instruction and hands-on practice in addition to oversight, is required to train non-physicians to perform endoscopy as safely and effectively as physicians. Additionally, the context in which the non-physician endoscopy program is organized will dictate key program characteristics including remuneration, participant recruitment and professional and legal considerations. This review explores the evidence in support of non-physician based endoscopy, potential challenges in implementing non-physician endoscopy and requirements for a high-quality program to support training and implementation.